2017
DOI: 10.1038/ismej.2017.37
|View full text |Cite
|
Sign up to set email alerts
|

Niche partitioning of diverse sulfur-oxidizing bacteria at hydrothermal vents

Abstract: At deep-sea hydrothermal vents, primary production is carried out by chemolithoautotrophic microorganisms, with the oxidation of reduced sulfur compounds being a major driver for microbial carbon fixation. Dense and highly diverse assemblies of sulfur-oxidizing bacteria (SOB) are observed, yet the principles of niche differentiation between the different SOB across geochemical gradients remain poorly understood. In this study niche differentiation of the key SOB was addressed by extensive sampling of active su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
178
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 149 publications
(199 citation statements)
references
References 115 publications
21
178
0
Order By: Relevance
“…In addition, a study within a single vent field at Axial Seamount showed differences in gene expression patterns between both diffuse vents as well as within the intra‐field waters between vent sites (Olins et al ., ). Finally, through the reconstruction of genomes from metagenomes (Tyson et al ., ; Dick et al ., ; Hug et al ., ), recent genomic binning studies at hydrothermal systems have revealed the presence of novel microbial and viral groups as well as their metabolic potential, including the discovery of auxiliary metabolic genes for sulfur oxidation within deep ocean viruses and the potential importance of hydrocarbon degradation distal to venting fluids, including within hydrothermal plumes (Anantharaman et al ., ; Li et al ., ; Sheik et al ., ; Meier et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In addition, a study within a single vent field at Axial Seamount showed differences in gene expression patterns between both diffuse vents as well as within the intra‐field waters between vent sites (Olins et al ., ). Finally, through the reconstruction of genomes from metagenomes (Tyson et al ., ; Dick et al ., ; Hug et al ., ), recent genomic binning studies at hydrothermal systems have revealed the presence of novel microbial and viral groups as well as their metabolic potential, including the discovery of auxiliary metabolic genes for sulfur oxidation within deep ocean viruses and the potential importance of hydrocarbon degradation distal to venting fluids, including within hydrothermal plumes (Anantharaman et al ., ; Li et al ., ; Sheik et al ., ; Meier et al ., ).…”
Section: Introductionmentioning
confidence: 97%
“…Recently, a number of metagenomic and metatranscriptomic studies of microbial communities within and around hydrothermal vents have led to new insights about the diversity of microbial metabolisms present and expressed under different geological and chemical conditions (e.g., Dick et al ., ; Urich et al ., ; Li et al ., ; Anantharaman et al ., ; Fortunato and Huber, ; Meier et al ., ; Reveillaud et al ., ; Olins et al ., ). For example, hydrothermal vent plumes sampled above the seafloor were shown to vary chemically and be taxonomically and metabolically distinct from seafloor vent fluid and subseafloor communities (Dick et al ., ).…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the described function in S. denitrificans , the soxY 2 Z 2 genes of the soxCD Y 2 Z 2 operon show a much higher level of diversification between different Sulfurimonas and Sulfurovum species (up to 79% nucleotide sequence dissimilarity) than soxY 1 Z 1 of the soxABXY 1 Z 1 operon (Meier et al ., ). Moreover, the sequence similarity between the two SoxYZ copies in S. denitrificans and other Campylobacteria is very low.…”
Section: Discussionmentioning
confidence: 97%
“…In fact, no significant identity, except for the export signal sequence, is detectable on the nucleotide level for either gene. This highly divergent intragenomic duplication, and the intergenomic diversification of the SoxY 2 Z 2 proteins, is present in all currently available Sulfurimonas and Sulfurovum genomes (Meier et al ., ). Furthermore, a significantly higher expression level of SoxY 2 Z 2 proteins when compared with SoxY 1 Z 1 proteins has been found in the metaproteomes of Campylobacteria ‐dominated biofilms forming on black‐smoker chimneys (Pjevac et al ., ).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation